EMPLOYEE PERFORMANCE ANALYSIS BEFORE AND AFTER TRAINING BASED ON LEVEL OF EDUCATION AT PT TRIO ABADI LPG RAYON PRINGSEWU - Zuriana Zuriana; Riyadini Riyan Utami; Besty Lilyana; Firnasari (Jurnal Ekonomi, 2022)
The problem that arises in this study is that the performance of employees before participating in the training has not reached the standard of ability. The use of time in carrying out tasks is less efficient and too time consuming due to a lack of understanding and knowledge about the use of administrative application technology. And also the education level of PT Trio Abadi employees is dominated by the high school level education level. This study aims to determine the differences in employee performance before and after attending training based on the level of education at PT Trio Abadi LPG Rayon Pringsewu. The type of research used in this research is a comparative research type with a quantitative approach. The population in this study were all employees of the administration department at PT Trio Abadi LPG who had attended the training totaling 31 people. The sampling technique used is saturated sampling. Thus the sample in this study amounted to 31 people. The data analysis method used is Paired Sample t-test. The results of this study indicate that there are differences in employee performance before attending training and after attending training.